Desalting Southern California: Comparing Seven Utilities' Experiences. Issue 11 (1st November 2014) - Owens, Eric; Davis, Emily; Hosseini, Turaj
Abstract : The search for a reliable and local supply of potable drinking water has spurred growth of desalting facilities in Southern California and elsewhere. Desalters built in the past two decades share many similarities and challenges in efficiently operating reverse osmosis technology.